PELATIHAN PEMBUATAN E-PEDOMAN KEGIATAN PENGABDIAN BERBASIS PEMBERDAYAAN MASYARAKAT (PBPMD) DENGAN PEMANFAATAN FLIP HTML - Nur Hasanah; Lusi Endang Sri Darmawati; Raudatul Jannah; Sitti Aisyah (Bajang Institute, 2024)
This service aims to utilize Flip HTML training on e-guidelines, the implementation of which coincides with STKIP PGRI Situbondo students carrying out Community Empowerment Based Service (PBPMD) activities in Tambak Ukir village. The method of activity carried out is in the form of training, the main target of which is educators in the village of Tambak Ukir, Kendit District, Situbondo Regency, with 6 schools established in one village. And obtained from feedback after events or service activities with the theme